The complex stellar system M 22: confirming abundance variations with high precision differential measurements. Issue 3 (13th August 2022) - McKenzie, M; Yong, D; Marino, A F; Monty, S; Wang, E; Karakas, A I; Milone, A P; Legnardi, M V; Roederer, I U; Martell, S; Horta, D
ABSTRACT: M 22 (NGC 6656) is a chemically complex globular cluster-like system reported to harbour heavy element abundance variations. However, the extent of these variations and the origin of this cluster is still debated. In this work, we investigate the chemical in-homogeneity of M 22 using differential line-by-line analysis of high-quality (R = 110 000, S/N = 300 per pixel at 514 nm) VLT/UVES spectra of six carefully chosen red giant branch stars. By achieving abundance uncertainties as low as ∼0.01 dex (∼2 per cent), this high precision data validates the results of previous studies and reveals variations in Fe, Na, Si, Ca, Sc, Ti, Cr, Mn, Co, Ni, Zn, Y, Zr, La, Ce, Nd, Sm, and Eu. Additionally, we can confirm that the cluster hosts two stellar populations with a spread of at least 0.24 dex in [Fe/H] and an average s-process abundance spread of 0.65 dex. In addition to global variations across the cluster, we also find non-negligible variations within each of the two populations, with the more metal-poor population hosting larger spreads in elements heavier than Fe than the metal-rich. We address previous works that do not identify anomalous abundances and relate our findings to our current dynamical understanding of the cluster. Given our results, we suggest that M 22 is either a nuclear star cluster, the product of two merged clusters, or an original building block of the Milky Way.